Food and Addiction: A Comprehensive Handbook - Brownell, Kelly D; Gold, Mark S (Oxford University Press, Incorporated, 2012)
Food and Addiction: A Comprehensive Handbook brings scientific order to the issue of food and addiction, spanning multiple disciplines to create the foundation for what is a rapidly advancing field and to highlight needed advances in science and public policy. The book assembles leading scientists and policy makers from fields such as nutrition, addiction, psychology, epidemiology, and public health to explore and analyze the scientific evidence for the addictive properties of food.